2004
DOI: 10.1038/sj.onc.1207609
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of c-myc proto-oncogene by WT1 protein

Abstract: The Wilms' tumor 1 gene (WT1) plays an essential role in urogenital development and malignancy. Through DNA binding, WT1 can either enhance or repress transcription depending on the context of the DNA-binding sites or the cell type in which it is expressed. WT1 is overexpressed in a variety of human cancers, including leukemia and breast cancer; in these diseases, the expression of WT1 is associated with a poor prognosis. To determine how WT1 affects c-myc expression in the context of breast cancer cells, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 33 publications
(35 reference statements)
2
60
1
1
Order By: Relevance
“…Although this has complicated the interpretation of Mig1 function (37,160,189,376,384,386,423), clearly the primary physiological role of Mig1 seems to be that of a negative regulator of glucose-repressed genes (e.g., SUC2 and GAL1). Interestingly, the Mig1 N-terminal zinc fingers are very similar to those in the C terminus of WT1 (257), a human tumor suppressor that collaborates with p53 to repress transcription and (like p53) also activates transcription (133,224,235,248,264,268,306,348). Mig1 and WT1 are both phosphoproteins, and PKA phosphorylation of WT1 appears to make an important contribution to its repressor function (323); the significance of a potential PKA target site found in the internal regulatory region of Mig1 is not yet known (257,270).…”
Section: Snf1-mediated Signal Transduction In Glucose Repression and mentioning
confidence: 98%
“…Although this has complicated the interpretation of Mig1 function (37,160,189,376,384,386,423), clearly the primary physiological role of Mig1 seems to be that of a negative regulator of glucose-repressed genes (e.g., SUC2 and GAL1). Interestingly, the Mig1 N-terminal zinc fingers are very similar to those in the C terminus of WT1 (257), a human tumor suppressor that collaborates with p53 to repress transcription and (like p53) also activates transcription (133,224,235,248,264,268,306,348). Mig1 and WT1 are both phosphoproteins, and PKA phosphorylation of WT1 appears to make an important contribution to its repressor function (323); the significance of a potential PKA target site found in the internal regulatory region of Mig1 is not yet known (257,270).…”
Section: Snf1-mediated Signal Transduction In Glucose Repression and mentioning
confidence: 98%
“…Wt1 has been previously reported to have direct or indirect effects on end points that are also regulated by progestins, including c-Myc (Han et al, 2004), cyclin D1 (Zapata-Benavides et al, 2002), cyclin E , p21…”
Section: Wt1 Is An Early Target Of Progestin Regulationmentioning
confidence: 99%
“…By contrast, other groups have found that Wt1 is not expressed in normal mammary cells (Loeb et al, 2001), but is overexpressed in 30-75% of breast cancers (Loeb et al, 2001;Miyoshi et al, 2002;Nakatsuka et al, 2006), and that Wt1 overexpression is correlated with poor prognosis (Miyoshi et al, 2002). In support of a role for Wt1 as a putative breast oncogene, overexpression of Wt1 enhances proliferation and its downregulation suppresses proliferation in breast cancer cells (Oji et al, 1999;Zapata-Benavides et al, 2002;Han et al, 2004;Tuna et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…25 The expression plasmid for wild-type human DLX5 (pcDNA3.1-WT DLX5, WT) was from Drs Joseph R. Testa and Jinfei Xu (Fox Chase Cancer Center, Philadelphia, PA, USA), pGL2-SNM includes the total conventional MYC promoter sequences, containing the two major transcription start sites, whereas pGL2-XNM has only one start site. 24 Two segments of mutant cDNA for human DLX5 Q186H (with a nucleotide substitution at position 558) were amplified by PCR with the primer sequences forward (F), 5 0 -CGGGATCCATGACAGGAGTGTTTGACAG-3 0 and reverse (R1), 5 0 -GATCTTTTGTTATGAAACCAGATTT-3 0 (near the 5') (bold and underline represent the mismatched base); forward (F1), 5 0 -GGTTTCATAACA AAAGATCCAAG-3 0 and reverse (R), 5 0 -CGGAATTCATAGAGTGTCCCGGAG GCCAG-3 0 (near the 3'), with wild-type plasmid DNA as a template.…”
Section: Plasmidsmentioning
confidence: 99%
“…25 Whole-exome sequencing DNA from patient II3 was subjected to whole-exome sequencing (Beijing Genome Institute, Shenzhen, China). Exome capture involved use of the SureSelect Human All Exon Kit (Agilent, Santa Clara, CA, USA), and sequencing involved the HiSeq2000 platform (Illumina, San Diego, CA, USA).…”
Section: Dna Isolationmentioning
confidence: 99%